Hydrocoloids Biofunctional Food from Seaweeds and Its Applications in Food Industry - Noviendri, Dedi; Fitri Hasrini, Reno (Warta Industri Hasil Pertanian, 2012)
Hydrocolloids have a wide array of functional prpperties in foods. The most hydrocolloids from seaweeds are carregeenan, alginate and agar. Carrageenan and agar are sulfates polysaccharides mainly extracted from red seaweeds (Rhodophyceae) while alginate is extracted from brown seaweeds (Phaeophyceae). Gelidium and Gracilaria are the main seaweeds for commercially producing agar. Kappaphycus and Euchema spcies are the main seaweeds for commercialy producing carrageenan. Then, Laminaria and Sargassum species are the main brown algae for commercially producing alginate. Furthermore, hydrocolloids from seaweeds or marine hydrocolloids are apllied in the food industry for their functional characteristics such as emulsifying, thickening, gelling, and stabilizing agent. All of these hydrocolloidsnamely, alginate, agar and carrageenan have received regulatory approvals from the European Council, the United States Food and Drug Administration, Food and Agriculture Organization, and Codex Alimantarius Commision.